1989
DOI: 10.1038/jcbfm.1989.114
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Determination of Calcium—Calmodulin Binding Predicts Neuronal Damage after Global Ischemia

Abstract: Summ ary: Since ionic Ca 2 + binds with intracellular cal modulin (CaM) before activating proteases, kinases, and phospholipases, demonstration of persistent Ca 2 + -CaM binding in neurons destined to show ischemic cellular in jury would support the concept that elevated intracellular Ca2+ plays a causative role in ischemic neuronal damage. In order to characterize Ca 2 + -CaM binding, we used a sheep anti-CaM antibody (CaM-Ab) which recognizes CaM that is not bound to Ca 2 + or brain target proteins. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Indeed, it has been previously reported that a persistent increase in the concentration of Ca 2ϩ -bound calmodulin, which is an active form of calmodulin, is associated with ischemic neuronal damage. 13) Furthermore, calmodulin antagonists have been shown to protect against hypoxia/hypoglycemia in organic hippocampal cultures. 14) We have developed a competitive calmodulin antagonist, 3-[2-[4-(3-chloro-2-methylphenylmethyl)-1-piperazinyl]-ethyl]-5,6-dimethoxy-1-(4-imidazolylmethyl)-1H-indazole dihydrochloride 3.5 hydrate (DY-9760e), which exerts a cytoprotective action against the cell death induced by a Ca 2ϩ ionophore 15) and ameliorates brain injury that occurs after transient and permanent focal ischemia in rats.…”
mentioning
confidence: 99%
“…Indeed, it has been previously reported that a persistent increase in the concentration of Ca 2ϩ -bound calmodulin, which is an active form of calmodulin, is associated with ischemic neuronal damage. 13) Furthermore, calmodulin antagonists have been shown to protect against hypoxia/hypoglycemia in organic hippocampal cultures. 14) We have developed a competitive calmodulin antagonist, 3-[2-[4-(3-chloro-2-methylphenylmethyl)-1-piperazinyl]-ethyl]-5,6-dimethoxy-1-(4-imidazolylmethyl)-1H-indazole dihydrochloride 3.5 hydrate (DY-9760e), which exerts a cytoprotective action against the cell death induced by a Ca 2ϩ ionophore 15) and ameliorates brain injury that occurs after transient and permanent focal ischemia in rats.…”
mentioning
confidence: 99%
“…15,17) DY-9760e is also capable of reducing the ischemic infarct volume when given up to 3 h after the onset of permanent MCA occlusion in rats. 20) Given a previous report showing that the Ca 2ϩ -bound calmodulin complex reaches maximal levels 4 h following cerebral ischemia, it is feasible that the therapeutic time window for DY-9760e is 3 h. 12) Taken together, it is plausible that the amelioration of ischemic brain injury with this drug is mediated by a calmodulin antagonistic action in the brain. Further studies are needed to evaluate the molecular mechanism by which this compound exerts neuroprotective functions.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that calmodulin plays a critical role in ischemic brain injury: (1) a persistent increase of Ca 2ϩ -bound calmodulin, which is an active form, after ischemic insults; (2) significant up-regulation of calmodulin gene expression in the CA1 pyramidal cell layer after cerebral ischemia; and (3) protection by calmodulin antagonists against hypoxic/hypoglycemia in organotypic hippocampal cultures. 12,14,44) Furthermore, there are reports that cells expressing PEP-19, a brain-specific negative regulator of calmodulin, or a mutant calmodulin with Ca 2ϩ -binding defects are resistant to apoptotic stimuli. 45,46) DY-9760e rescues cultured neurons from a wide variety of cell-toxic stimuli that increase intracellular Ca 2ϩ , including excitotoxicity, voltage-gated channel opening, Ca 2ϩ ionophore, and inhibition of endoplasmic reticulum Ca 2ϩ -ATPase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocytochemical staining studies were performed exactly as described previously (Picone et al, 1989).…”
Section: Calmodulin Immunostainingmentioning
confidence: 99%